Reproduction of the invasive largemouth bass Micropterus salmoides (Lacepède, 1802) in a Neotropical reservoir with suggestions to management and control - Matheus Oliveira Freitas; Vanessa Maria Ribeiro; Vinícius Abilhoa; Jean Ricardo Simões Vitule (Acta Limnologica Brasiliensia, 2023)
Abstract Aim The largemouth bass Micropterus salmoides was introduced in more than 50 countries for the purpose of sport fishing. In Brazil, records date from 1922, and nowadays many populations are known to occur in the southern region. Here we investigated the reproductive biology of this species in a small reservoir in southern Brazil, to understand the role of the reproductive strategy in the invasion process and assist in its management. We conclude with suggestions for the management in local scale, as this species can bring relevant problems to the public supply through trophic cascade and other negative effects. Methods Samples were performed with different methods, between May 2011 and April 2012. All fishes were measured, and the reproductive season was determined through the relative frequency of reproductive stages and the gonadosomatic index. Sex ratio was calculated monthly and for each total length (TL) class and compared with the estimates presented in the literature. Total length at maturity (L50, length at which 50% of the individuals were mature) was estimated for females, males and the entire study population. Results A total of 565 individuals of M. salmoides were analyzed. Overall sex-ratio did not differ significantly. The monthly distribution of the gonadosomatic index for females and males showed higher values between August (late winter) and November 2011 (austral spring). -Binomial modelling of sex-ratio data of native (n=1) and introduced populations (n=7) showed a lower proportion of females in its native range. All individuals > 21.5 cm TL were mature (L95), and L50 was calculated at 18.7 cm TL. After the reproductive period, an increase in the abundance of young individuals (≤ 7.0 cm TL) was registered, corresponding to 50% of all individuals collected. The relative frequency of mature individuals and the variation in the gonadosomatic index indicate a prolonged spawning period during the austral spring, coinciding with the increase in temperature. Conclusions Results suggested that some changes in life history traits, such as the early sexual maturation and the long reproductive period, coupled with a remarkable adaptability, may have facilitated the establishment of M. salmoides populations in this reservoir. The illegal and intentional stocking by anglers plays a central role in the introduction and dispersal of M. salmoides in Brazil. We encourage studies on the sanitary quality of this fish for human consumption, so that massive campaigns of education the population to encourage capture and consumption are implemented by the competent authorities as a control measure in local scale, combined with targeted samplings with artificial baits during the reproductive period, identification, and removal of nests and fingerlings using electric fishing or trap nets during the recruitment period.